Case management of patients who frequently present to a Scottish emergency department. Issue 2 (22nd January 2009) - Skinner, J; Carter, L; Haxton, C
Abstract : Aims: To assess whether case management of frequent attenders to the emergency department (ED) reduces subsequent attendances made by these patients. Methods: Patients who attended the ED 10 times or more over a 6-month period were identified. Their cases were assessed and care plans put in place, if appropriate. Patient attendances over the subsequent 6 months were compared. Results: 57 patients attended the ED 10 times or more over the 6-month period (1.4% of the departmental workload). The median number of ED attendances in this patient group was 12.0 (interquartile range (IQR) 10–14). In the subsequent 6 months following case management of these patients, median attendances in the same 57 patients dropped to 6.0 (IQR 2–13, p<0.001). The total number of attendances in this patient group dropped from 720 to 499, a reduction of 31%. Conclusions: The findings of this study suggest that individual case management and implementation of care plans may help to reduce subsequent attendances in patients who frequently attend ED.